2023
DOI: 10.3389/fimmu.2023.1186369
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-specific binding of 8-oxoguanine DNA glycosylase 1 (OGG1) reprograms mucosal adaptations to chronic airway injury

Abstract: Recent advances have uncovered the non-random distribution of 7, 8-dihydro-8-oxoguanine (8-oxoGua) induced by reactive oxygen species, which is believed to have epigenetic effects. Its cognate repair protein, 8-oxoguanine DNA glycosylase 1 (OGG1), reads oxidative substrates and participates in transcriptional initiation. When redox signaling is activated in small airway epithelial cells, the DNA repair function of OGG1 is repurposed to transmit acute inflammatory signals accompanied by cell state transitions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 116 publications
0
2
0
Order By: Relevance
“…Additionally, it was shown that DNA-bound OGG1 at 8-oxoGua interacted with mitogen-and stress-activated kinase 1, which phosphorylates NFκB/RelA at serine 276, inducing expression of innate cytokines and chemokines [ 46 ]. A recent study documented that OGG1 at 8-oxoGua in the context of chromatin recruited phosphorylated SMAD2/3 complex and NFκB to their cognate binding sequence located in promoters of tissue remodeling genes including alpha-smooth muscle actin (α-SMA), collagen (COL), and fibronectin (FN) for excessive gene expression [ 41 , 47 ]. Another recent study revealed that Myc oncogene binding to the E-box promoter recognition sequence required OGG1 under oxidative stress conditions [ 48 ].…”
Section: Ogg1 Induces Dna Remodeling In Proximity Of Transacting Fact...mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it was shown that DNA-bound OGG1 at 8-oxoGua interacted with mitogen-and stress-activated kinase 1, which phosphorylates NFκB/RelA at serine 276, inducing expression of innate cytokines and chemokines [ 46 ]. A recent study documented that OGG1 at 8-oxoGua in the context of chromatin recruited phosphorylated SMAD2/3 complex and NFκB to their cognate binding sequence located in promoters of tissue remodeling genes including alpha-smooth muscle actin (α-SMA), collagen (COL), and fibronectin (FN) for excessive gene expression [ 41 , 47 ]. Another recent study revealed that Myc oncogene binding to the E-box promoter recognition sequence required OGG1 under oxidative stress conditions [ 48 ].…”
Section: Ogg1 Induces Dna Remodeling In Proximity Of Transacting Fact...mentioning
confidence: 99%
“…Exposure of cells to increased oxidative stress provides a powerful stimulus to NFκB-driven gene regulation [ 75 ]. This is exemplified by NFκB interaction with OGG1 [ 35 , 47 , 76 ], which redirects NFκB activity and impairs immunity [ 76 ]. In contrast, enzymatically active OGG1 guards genome integrity through either lesion repair or elimination of cells with malignant potential, to maintain the homeostasis of the host, which might depend on the magnitude of guanine oxidation [ 77 ].…”
Section: Oxidative Stress As a Driver For Cancer Plasticitymentioning
confidence: 99%
“…As such, the 8-oxoG chemical modification has garnered interest for study as a biomarker of oxidative stress. In human DNA, 8-oxodG damage is corrected by the base excision repair protein, 8-oxoguanine DNA glycosylase (OGG1) [19][20][21]. However, despite RNA being more susceptible to oxidative damage than DNA [22,23], such a mechanism for oxidative damage repair in human RNA remains unknown.…”
Section: Introductionmentioning
confidence: 99%